2021
DOI: 10.15406/jamb.2021.10.00309
|View full text |Cite
|
Sign up to set email alerts
|

Age structure of non-native fish species, Cyprinus carpio (Linnaeus, 1758) from the tributary of the Ganga river, India

Abstract: Cyprinus carpio (e.g. culture and wild/capture) constitute a large part of daily meal of human population in Indian sub-continent. It shows benthic and sedentary behavior. Age structure of C. carpio was studied during February 2019 to January 2020 from fish landing centre at Sirsa, Prayagraj, Uttar Pradesh, India. The key scales were studied for estimation of age structure in the present study. A total of 548 fish specimens in length ranges between 97 to 687 mm and age classes of 0+ to 9+ were observed. Age st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…We found that male carp are more impacted by KHVD associated morbidity and mortality than females in the carp populations we investigated. Carp populations in similar ecoregions and worldwide have generally been reported to have equal proportions of male and female carp or a higher proportion of males (Devlin, 1999; Dwivedi & Mayank, 2013; Fernndez‐Delgado, 1990; Swee & McCrimmon, 1966; Tessema et al, 2020); however, the CyHV‐3‐positive populations surveyed here were female dominated. Acute infections were more common in male fish in Elysian in 2019 and 2020 and dead carp with high CyHV‐3 viral loads in 2019 were almost exclusively male.…”
Section: Discussionmentioning
confidence: 67%
“…We found that male carp are more impacted by KHVD associated morbidity and mortality than females in the carp populations we investigated. Carp populations in similar ecoregions and worldwide have generally been reported to have equal proportions of male and female carp or a higher proportion of males (Devlin, 1999; Dwivedi & Mayank, 2013; Fernndez‐Delgado, 1990; Swee & McCrimmon, 1966; Tessema et al, 2020); however, the CyHV‐3‐positive populations surveyed here were female dominated. Acute infections were more common in male fish in Elysian in 2019 and 2020 and dead carp with high CyHV‐3 viral loads in 2019 were almost exclusively male.…”
Section: Discussionmentioning
confidence: 67%
“…[42] Dwivedi and Mayank (2013) reported that the C. carpio attained an average length of 19.0, 26.7, 37.5, 41.1, 45.5, 49.6, 54.9, 59.5, 63.1, 66.2, 70.9 and 76.2 cm, respectively at the end of 1+ to 12+ years of the life cycle from the Yamuna River, Uttar Pradesh, India. Several factors can account for the fluctuation in the age and growth rate as like quantity and quality of available food, the richness of species, density of exotic species (Example especially Cyprinus carpio) quality of the water (For example organic load, heavy metal concentration), maturity and spawning cycle [57][58][59][60][61][62][63][64][65][66][67][68][69]. This species can typically live for around 20 years in the wild freshwater ecosystem (for example rivers) [70][71].…”
Section: Resultsmentioning
confidence: 99%
“…It is distributed throughout countries in Asian countries as like India, Pakistan, Bangladesh, Burma and Nepal and also globally spread [21,22]. It is economically important fish species from the Tons River and also Ganga River system, and supports an important commercial fishery in rivers, reservoirs, lakes and even in culture ponds [23][24][25]. C. carpio is a non-native fish species for India.…”
Section: Introductionmentioning
confidence: 99%